Prevalence and clinical relevance of helminth co-infections among tuberculosis patients in urban Tanzania - Francis Mhimbira; Jerry Hella; Khadija Said; Lujeko Kamwela; Mohamed Sasamalo; Thomas Maroa; Magreth Chiryamkubi; Grace Mhalu; Christian Schindler; Klaus Reither; Stefanie Knopp; Jürg Utzinger; et al. (2017)
Background Helminth infections can negatively affect the immunologic host control, which may increase the risk of progression from latent Mycobacterium tuberculosis infection to tuberculosis (TB) disease and alter the clinical presentation of TB. We assessed the prevalence and determined the clinical relevance of helminth co-infection among TB patients and household contact controls in urban Tanzania. Methodology Between November 2013 and October 2015, we enrolled adult (≥18 years) sputum smear-positive TB patients and household contact controls without TB during an ongoing TB cohort study in Dar es Salaam, Tanzania. We used Baermann, FLOTAC, Kato-Katz, point-of-care circulating cathodic antigen, and urine filtration to diagnose helminth infections. Multivariable logistic regression models with and without random effects for households were used to assess for associations between helminth infection and TB. Principal findings A total of 597 TB patients and 375 household contact controls were included. The median age was 33 years and 60.2% (585/972) were men. The prevalence of any helminth infection among TB patients was 31.8% (190/597) and 25.9% (97/375) among controls. Strongyloides stercoralis was the predominant helminth species (16.6%, 161), followed by hookworm (9.0%, 87) and Schistosoma mansoni (5.7%, 55). An infection with any helminth was not associated with TB (adjusted odds ratio (aOR) 1.26, 95% confidence interval (CI): 0.88–1.80, p = 0.22), but S. mansoni infection was (aOR 2.15, 95% CI: 1.03–4.45, p = 0.040). Moreover, S. mansoni infection was associated with lower sputum bacterial load (aOR 2.63, 95% CI: 1.38–5.26, p = 0.004) and tended to have fewer lung cavitations (aOR 0.41, 95% CI: 0.12–1.16, p = 0.088). Conclusions/Significance S. mansoni infection was an independent risk factor for active TB and altered the clinical presentation in TB patients. These findings suggest a role for schistosomiasis in modulating the pathogenesis of human TB. Treatment of helminths should be considered in clinical management of TB and TB control programs.